OIL RESOURCE ABUNDANCE AND SECTORAL PERFORMANCES IN NIGERIA, 1970 - 2010 (2014)
Oil Resource Abundance (ORA) has dominated the Nigerian revenue since the 1970s, contributing over 70.0%. Empirical literature have focused on the effects of ORA on aggregate macroeconomic variables (annual average growth in export to import price ratio, agricultural output growth rate, manufacturing output growth rate, public consumption, exchange rate and trade openness), while little attention has been devoted to the multi-sectoral dimension of the effects. This study, therefore, examined the effects of ORA on sectoral investment and output in Nigeria between 1970 and 2010. A macroeconometric model, predicated on the ‘Dutch disease’ theoretical framework was estimated. The framework recognised how a booming sector can hamper growth in the activity sectors (agriculture, services, building and construction, and manufacturing) of the economy. The model considered the linkages between ORA and the activity sectors and ORA was measured as the ratio of revenues from oil to total government revenues. Three Stage Least Squares estimation technique that took cognisance of serial error correlation among the equations in the system, and controlled for endogeneity in the presence of sector-specific effects was employed. Simulation of the model was performed for both ex-post and ex-ante forecasting under different policy scenarios. The data were collected from Central Bank of Nigeria’s Statistical Bulletin, Nigerian National Petroleum Corporation’s Annual Statistical Bulletin and World Development Indicators. Statistical tests for internal consistency using Theil’s inequality coefficients and its decomposition, as well as graphical representations that compared the actual and predicted values of the endogenous variables were carried out to ascertain the model’s forecast accuracy. A 1.0% increase in ORA significantly led to diverse effects on the sectors through public spending channel. Investment dropped in agriculture (4.3%) and services (1.1%) and improved in manufacturing sector (5.2%) and building and construction sector (0.2%). Output declined in agricultural sector (0.5%), services sector (0.3%) and increased in manufacturing sector (0.6%) and building and construction sector (0.5%). For ex-ante forecast of 5.0% increase in ORA, investment declined in agriculture (1.0%), manufacturing (0.5%), services (0.4%), and building and construction (0.4%). Output decreased in services (0.1%) and agriculture (0.1%) and rose in building and construction (0.2%) and manufacturing (0.2%). Under the forecast scenario of 5.0% decrease in ORA, investment increased in all the sectors (services-0.8%, agriculture-0.5%, building and construction-0.2% and manufacturing-0.1%). Output rose in services (0.1%) and agriculture (0.01%) and declined in building and construction (0.2%) and manufacturing (0.04%). Oil resource abundance had negative and positive impacts on the activity sectors of the economy. The negative impact was indicative of the presence of the ‘Dutch disease’ syndrome while the positive implied growth in national earnings through a favourable shift in the production activities of the sectors involved. There is the need, therefore, for the government to diversify the economy in order to enhance investment and output in the activity sectors.